(untitled) (Journal Of Educational and Psychological Researches, 2023)
The research aims to build a training program to develop the willpower in the kindergarten children. In order to achieve the objective of the research, the two researchers have developed a Training Program according to the following steps: - Determining the general objective of the Training Program. - Determining the behavioral objectives of the Training Program. - Determining the content of the Training Program. - Implementing the content of the Training Program sessions. - Evaluating the Training Program. The training program consisted of (15) sessions, each session included a set of parts (title, general objective, methods, time and place to implement the sessions, behavioral goals, tools and means, content, application, and evaluation).